Analysis data for development of multifunctional computer-aided rhinomanometer - Аврунін, О. Г.; Farouk, H. (ХНУРЭ, 2011)
Dept. of BME, Alaflaj Community College of Alkharj University, Saudi Arabia A scheme of modern multifunctional rhinomanometer is proposed. The role of main parameters (airflow, pressure, respiratory resistance and power of nasal airway) and diagnostic criteria for functional diagnostics of upper respiratory airway diseases are described. Principles of design and components of multifunctional rhinomanometer are discussed. Diagnostic possibilities of the rhinomanometer for evidence-based medicine conception are described.